Malaysian Code of Corporate Governance: One more perspective of scoring the best compliance of corporate governance by Malaysian listed companies. - Mok, Kam Wah (2004)
Worldwide public listed company scandals, failures and breakdown in fair and truthful accounting had undermined investing public faith in corporate leadership, financial reporting by directors and external auditors, and the integrity of the securities markets.The general consensus view is that to attract foreign capital inflows into one economy it must have the basis elements of good corporate governance. Good corporate governance would secure a strong and health public listed companies which in turn a strong and health economy for a country. The circumstances in Malaysia precipitating good corporate governance principles and practice largely arose from the global listed company scandals and the Asian Economic downturn that happened swiftly in mid-1997. It had prompted the formation of a “high level Finance Committee on Corporate Governance”, which sets out broad principles and practices of good corporate governance for Malaysian public listed companies. Firstly, the paper evaluates the level of compliance with the Malaysian Code by the first 100 top public listed companies by market capitalization on the 29 August 2003 on the KLSE. To do this a Corporate Governance Scorecard was developed. The finding shows an overall high level of compliance with the Code mainly due to the fact that most of the recommendation of the Malaysian Code has been adopted by the KLSE as listing requirements. The paper found that there is no significant relationship between corporate governance scores and company major shareholder or owner, namely government-owned, familyowned and foreign-owned. However, it founds that at least one of the three company attributes including company age, company size and company profitability is related to the corporate governance scores. The final regression test found that at least one of the five governance mechanisms is statistically related to the company performance.